Age of onset, nutritional determinants, and seasonal variations in menarche in rural Bangladesh. - Rah JH; Shamim AA; Arju UT; Labrique AB; Rashid M; Christian P; Rah, Jee H; Shamim, Abu Ahmed; Arju, Ummeh T; Labrique, Alain B; Rashid, Mahbubur; Christian, Parul (Journal of Health, Population & Nutrition, 2009)
Menarche is an important milestone in the development of female adolescents. The study assessed the age at menarche using recall, its seasonality, and association with marital and nutritional status (using mid-upper arm circumference [MUAC]) among 3,923 female adolescents aged 12-19 years in a rural area of Bangladesh. At the time of assessment, most (88%) adolescents had attained menarche at the mean (standard deviation [SD]) age of 12.8 (1.4) years. Age of onset of menarche among married adolescents (13%) occurred earlier than in those who were unmarried (12.6 +/- 1.3 years vs 12.9 +/- 1.4 years, p < 0.01). Age at menarche was negatively associated with MUAC after adjusting for age and marital status (beta = -0.10, p < 0.01). More than 50% of the adolescents had an onset of menarche during winter (chi2 = 634.97; p < 0.001), with peaks in December and January. In this rural population, the current age at menarche was found to be slightly lower than the previous estimates of 13.0 years in Bangladesh. An early onset of menarche was associated with season and better nutritional status of the female adolescents and may be associated with early marriage.